Phenotypic and genetic relationship of Acinetobacter Baumannii isolates - E. Trajkovska Dokic; V. Kotevska; A. Kaftandzieva; G. Jankoska; G. Mircevska; M. Petrovska; N. Panovski (Македонска академија на науките и уметностите, Одделение за биолошки и медицински науки = Macedonian Academy of Sciences and Arts, Section of Biological and Medical Sciences, 2011)
The interest in Acinetobacter continues to rise. One of the main reasons is the emergence of multi-resistant strains, which cause outbreaks of infection involving several patients in a ward, in the intensive care unit and in different areas of the hospital. Many outbreaks of its infection or colonization in surgical, neonatal and burn intensive care units have been reported, but the epidemiology of these infections remains unclear. Aim: To investigate the relationship among the isolates of Acinetobacter baumannii, comparing some of their phenotypic and genetic features. Material and methods: A total of 20 Acinetobacter baumanni isolates were included in the study. 12 strains of Acinetobacter baumannii were obtained within a week in July 2010, from neonates hospitalized at the paediatric intensive care unit and on the neonatal ward. Three strains were isolated from neonates at the paediatric intensive care unit three months ago. All the Acinetobacter baumannii strains were isolated from tracheal aspirates obtained from neonates with infection of the lower respiratory tract. Five additional Acinetobacter baumannii strains were included in the study as controls. They were isolated from wound swabs taken from adult patients with wound infection, hospitalized at the University Traumatology Clinic. Susceptibility of the bacterial strains to 13 different antimicrobial agents was determined by the disk diffusion method (Kirby-Bauer). Additional testing of the susceptibility was performed by the VITEK 2 system. RAPD-PCR fingerprinting was carried out using the following primer (5' GAAACAGCTATGACCATG -3'). Results: All A. baumannii isolates were multi-drug resistant. Antibiotic susceptibility-testing by the disk-diffusion method and automated VITEK 2 system showed 3 and 2 antimicrobial susceptibility patterns, respectively. RAPD-PCR assay of A. baumannii strains revealed two different RAPD-fingerprints. All the strains of A. baumannii isolated within a week in July 2010 from tracheal aspirates taken from neonates in the paediatric intensive care unit and neonates in the paediatric ward revealed the same RAPD-fingerprint, as well as 3 strains of A. baumannii isolated from tracheal aspirates taken from neonates in the paediatric intensive care unit three months ago. 5 strains of A. baumannii isolated from wound swabs of patients hospitalized at the Traumatology Clinic revealed a different RAPD-fingerprint. Conclusion: All the strains of A. baumannii isolated from neonates in the paediatric intensive care unit and paediatric ward were multi-drug resistant. Investigating the resistance patterns in multi-resistant isolates of Acinetobacter is a useful method which can predict the strain relationship. This method could be completed by at least one molecular method, such as the RAPD-PCR technique, which has shown itself to be a convenient and more reliable in interpreting the strain relationship of the A. baumannii isolates. Good infection control procedures, including phenotypic and molecular typing of A. baumannii isolates, are essential for preventing outbreaks of multi-drug resistant A. baumannii infections in our hospitals.
Keywords: Acinetobacter baumannii; Phenotypic relationship; Genetic relationship; Resistance patterns; RAPD-PCR fingerprints